Improve the chewing quality of patients with partial edentulous accompanied by severe mastication and aesthetic disorders: Meningkatkan kualitas pengunyahan penderita edentulus parsialis disertai gangguan mastikasi dan estetik yang parah - Hermawati, Desi; Jubhari, Eri Hendra; Taqwim, Aksani (Makassar Dental Journal PDGI Makassar, 2024)
Mastication and aesthetic disturbances are often experienced by patients with multiple anterior and posterior tooth losses. In the case of patients with few remaining natural teeth, a telescopic overdenture may be a potential option. This will improve the stability and retention of the prosthesis. This article reports the management of a patient with partial edentulous with severe mas-ticatory and aesthetic impairment using a telescopic overdenture prosthesis to improve chewing quality and aesthetics. A 70-year-old woman came to the Prosthodontics Clinic with complaints of difficulty chewing and lack of confidence due to the loss of most of the teeth in the upper jaw and lower jaw and the upper front teeth were slightly loose. The patient wanted to have a denture made so that she could chew food well and improve her smile. After a thorough examination, the patient was treated with an overdenture and four telescopic crowns were placed on the anterior abutment teeth. It was concluded that the use of telescopic overdenture in patients with edentulus parsialis can improve aesthetics and masticatory quality.